PEDAGOGICAL BASICS OF PREPARING FUTURE TEACHERS FOR THE DEVELOPMENT OF NATIONAL AND GENERAL CULTURAL COMPETENCIES IN STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the forms of preparation of future teachers for the development of national and general cultural competences in students are studied, its necessity and pedagogical foundations are detailed.